(DIS)SATISFACTION OF HUMAN NEEDS OF OLDER ADULTS DURING THE COVID – 19 PANDEMIC - Rodríguez Martínez, Carlos Vicente (2021)
The article responds to a descriptive – analytical research on human needs and quality of life of older adults in the pandemic context of COVID-19. The definitions and theoretical elaborations coming mainly from the social sciences were taken. The objective of the study is to analyze the (dis)satisfaction of needs as an expression of the quality of life of a group of older adults in Havana, Cuba, during the pandemic context of COVID - 19. From a mixed methodological perspective (quantitative-qualitative) it was possible to respond to the research problem. The research techniques used were the interview and the questionnaire, applied to a sample of older adults residing in Havana, the second oldest province in Cuba. Among the most important results, it was corroborated that the quality of life of this age group has worsened as a result of the dissatisfaction of notable human needs during the pandemic context and the implementation of theTarea Ordenamiento.